Enabling economic independence among rural women through self-help groups: Evidence from the Samridh Tejeshwani initiative - Shikha Dhawan; Rinki Kumari; Swapan Suman; Sushil Kumar Sharma; Sudheer Nadipally (Dynamics of Rural Society Journal, 2026)
Rural women in India continue to face persistent socio-economic challenges, including limited financial inclusion, inadequate opportunities for skill development, and weak market linkages, which significantly restrict income generation and decision-making autonomy. Addressing these barriers is essential to achieving inclusive rural development and gender equity. Against this backdrop, the present study examines the role of Self-Help Groups (SHGs) in empowering rural women—referred to in this study as Samridh Tejeshwanis, denoting economically independent and socially empowered SHG members. This study aimed to develop and evaluate sustainable SHG-based livelihood models capable of enhancing women’s income, leadership, and collective decision-making through structured interventions in skill training, enterprise development, production, and market integration. A mixed-methods approach was employed, integrating qualitative evidence from field observations, interviews, and focus group discussions with quantitative analysis of pre- and post-intervention income data collected from nine SHGs across seven villages. Key interventions included vocational skill enhancement, financial literacy training, branding and packaging support, digital marketing facilitation, and convergence with government livelihood schemes. The findings indicate significant socio-economic gains, with the average monthly income of SHG members increasing by 61–80% following the interventions. In addition to income growth, members demonstrated marked improvements in communication skills, self-confidence, leadership, and collective decision-making. Enhanced social recognition and greater participation in community and panchayat-level activities were also reported. Overall, the study demonstrates that targeted and integrated SHG interventions can create sustainable pathways for women’s economic independence, strengthen social capital, and provide a scalable and replicable model for gender-inclusive rural livelihood development in India. These findings highlight the value of integrating capacity-building, market support, and policy convergence to accelerate gender-inclusive rural growth.